Combined education and skin antisepsis intervention for persistently high blood-culture contamination rates in neonatal intensive care. Issue 1 (May 2016) - O'Connor, C.; Philip, R.K.; Powell, J.; Slevin, B.; Quinn, C.; Power, L.; O'Connell, N.H.; Dunne, C.P.
Summary: Contaminated blood cultures represent challenges regarding diagnosis, duration of hospitalization, antimicrobial use, pharmacy and laboratory costs. Facing problematic neonatal blood culture contamination (3.8%), we instigated a successful intervention combining skin antisepsis using sterile applicators with 2% chlorhexidine gluconate in 70% isopropanol prior to phlebotomy (replacing 70% isopropanol) and staff education. In the six months prior to intervention, 364 neonatal peripheral blood samples were collected. Fourteen (3.8%) were contaminated. In the post-intervention six months, 314 samples were collected. Three (0.96%) were contaminated, representing significant improvement (Fisher's exact test: P  = 0.0259). No dermatological sequelae were observed. The improvement has been sustained.